Immunopathogenesis of Acute Pancreatitis - G. V. Bulava (Неотложная медицинская помощь, 2022)
The leading positions in terms of frequency, severity of the course and high mortality belong to infectious forms of acute pancreatitis. However, not all pathophysiological mechanisms of the development of this disorder have been studied. Given that immune responses are an integral part of the pathogenesis of pancreatitis, it is extremely important to study the relationship between the mechanisms of inflammation and activation of the immune response. This review will discuss the role of various populations of innate immune cells, including macrophages, neutrophils, dendritic and mast cells, and regulatory immune cells in the pathogenesis of gland tissue destruction and the relationship between immune responses and systemic inflammatory response syndrome. Targeting innate immune cell populations and metabolite signaling pathways in acute pancreatitis may lead to a broader and ultimately more effective redirection of the treatment program towards disease resolution and improved clinical outcomes.